Application of Eco-Friendly Activated Carbon from Organic Waste for Polluted River Water Treatment: Kinetic Study and Water Quality Evaluation - Mawarni, Mintan; Triwuri, Nurlinda Ayu; Fadlilah, Ilma (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Universal, 2025)
River water pollution in Cilacap Regency is caused by industrial activities related to oil refining and river crossing traffic, which generate wastewater containing Total Suspended Solids (TSS), Total Dissolved Solids (TDS), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and heavy metals such as lead. This study aims to evaluate the performance of biomass-based activated carbon—derived from coconut fronds and laban wood sawdust—in river water purification through physicochemical characterization and adsorption kinetics approaches. The activated carbon was characterized according to the Indonesian National Standard (SNI) 06-3730-1995, and its surface area was analyzed using the Brunauer–Emmett–Teller (BET) method. Characterization results for AC-PK 1(100) showed a moisture content of 0.1085%, ash content of 3.05%, iodine adsorption capacity of 571 mg/g, and a surface area of 110.595 m²/g. The adsorption process after 15 minutes demonstrated that the activated carbon was effective in reducing water quality parameters, with the pH reaching neutral (7) and TSS decreasing to 212 mg/L, meeting Class III standards based on Government Regulation No. 82 of 2001. However, the TDS value of 4690 mg/L did not meet the quality standard. Kinetic studies indicated that the first-order reaction model best described the adsorption mechanism, with R² values approaching 1. The adsorption rate constants were 0.0041 min⁻¹ for TSS and 0.0686 min⁻¹ for TDS. These findings suggest the potential application of biomass waste as a raw material for activated carbon in environmentally friendly river water purification technologies.